2012
DOI: 10.1186/1471-230x-12-80
|View full text |Cite
|
Sign up to set email alerts
|

Capsule colonoscopy increases uptake of colorectal cancer screening

Abstract: BackgroundScreening colonoscopy effectiveness is hampered by limited adherence by the general population. The present prospective study was performed to evaluate whether adding capsule colonoscopy to the endoscopic screening options increases uptake.MethodsInvitation letters were sent to 2150 persons above the age of 55 insured with a German medical insurance company in the area of Rinteln, Lower Saxony with a baseline spontaneous annual screening colonoscopy uptake of 1 %. Both capsule or conventional colonos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 27 publications
0
39
1
5
Order By: Relevance
“…The trial registered as ClinicalTrials.gov number NCT01557101 complied with the CONSORT extension for pragmatic trials. 19 Inclusion criteria were: asymptomatic FDR ≥40 years of age or ten years less than the youngest relative with CRC. Exclusion criteria were: previous CRC screening; history of colorectal neoplasia or inflammatory bowel disease; hereditary CRC; gastrointestinal surgery; pregnancy; allergy or other severe comorbidity (mean life expectancy of <5 years) or major limitation of physical activity (performance status ≥2); and contraindication for bisacodyl, polyethylen glycol or phosphates.…”
Section: Subjectsmentioning
confidence: 99%
“…The trial registered as ClinicalTrials.gov number NCT01557101 complied with the CONSORT extension for pragmatic trials. 19 Inclusion criteria were: asymptomatic FDR ≥40 years of age or ten years less than the youngest relative with CRC. Exclusion criteria were: previous CRC screening; history of colorectal neoplasia or inflammatory bowel disease; hereditary CRC; gastrointestinal surgery; pregnancy; allergy or other severe comorbidity (mean life expectancy of <5 years) or major limitation of physical activity (performance status ≥2); and contraindication for bisacodyl, polyethylen glycol or phosphates.…”
Section: Subjectsmentioning
confidence: 99%
“…Vor allem bei der risikoadaptierten Darmkrebsfrüherkennung hat es lange gedauert, bis die Einsicht wuchs, dass v. a. bei familiärem Darmkrebsrisiko oder genetischem Risiko ein früherer Beginn der Vorsorgeuntersuchungen zwingend ist. Nachdem die S3-Leitlinien der Fachgesellschaften zum kolorektalen Karzinom dies eindeutig formuliert und den Zeitrahmen deutlich früher gelegt haben, besteht heute kein Zweifel mehr daran, dass bei einem derart Betroffenen mindestens 10 Jahre vor dem Erkrankungsalter des Indexpatienten eine Darmspiegelung erfolgen sollte [10]. Das KFRG trägt dieser Entwicklung mit der Möglichkeit der Flexibilisierung der Altersgrenzen durchaus Rechnung.…”
Section: Aktivitäten Der Krankenkassenunclassified
“…In a prospective study performed in Germany to examine whether colon capsule endoscopy could increase adherence to screening colonoscopy in a healthy population Groth et al found that offering capsule endoscopy led to a fourfold increase of screening uptake compared to standard colonoscopy [10].…”
Section: Can Colon Capsule Endoscopy Play a Role In Clinical Medicinementioning
confidence: 99%